Decolonial gesture as pedagogical method: theatrical practices in Brazil and Peru (Urdimento: Revista de Estudos em Artes Cênicas, 2019)
This article seeks to circumscribe pedagogy through the notion of “decolonial gesture.” For that, the artistic-pedagogical practices of Yuyachkani (Peru) and Ói Nóis Aqui Traveiz (Brazil) are taken up as forms of resistance and elements through which to break the coloniality of power relations and knowledge. Applying Walter Mignolo's concepts of colonial difference, coloniality and liminal thinking, this article demonstrates how this gesture of resistance against coloniality helps constitute autonomous subjects and subjectivities. The work of these two Latin American groups is problematised, characterising their practices as decolonial theatrical gestures and pedagogies.